Analisis Potensi Daya Listrik PLTS Atap di Gedung K4 Universitas Negeri Surabaya - Wardani, Ayusta Lukita; Aribowo, Widi; Widiyartono, Mahendra; Rahmadian, Reza; Hermawan , Aditya Chandra; Laksmi B, Nur Vidia (Elposys: Jurnal Sistem Kelistrikan, 2024)
In order to utilize the potential of solar energy and support the government in its energy transition efforts and achieve Net Zero Emissions, it is necessary to utilize solar power plants more massively. One thing that can be done is the installation of solar panels on the roof of a building called Rooftop PLTS. This rooftop PLTS is designed on the roof of the K4 Unesa building with an ongrid system because lecture activities only exist from morning to evening. Research conducted to analyze the potential of electrical energy on the roof of the K4 building using OpenSolar software. From the simulation results, the roof of the K4 building can be designed to install 70 solar panels with the LR4-72HPH-450M type and 5 Goodwe GW5K-DT type inverters which can produce 35,478 kWh per year with a PLTS capacity of 31,500 Wp. From the shadow simulation results, it is found that the selected location is optimal because there are no shadows of other buildings, trees or shadows from the solar panels themselves. Then from the POA analysis, it is found that between April to September has a relatively large amount of generation while in February the lowest energy is generated.